Search for high-mass diphoton states and limits on Randall-Sundrum gravitons at CDF. - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We have performed a search for new particles which decay to two photons using 1.2 fb(-1) of integrated luminosity from pp[over] collisions at square root s = 1.96 TeV collected using the CDF II detector at the Fermilab Tevatron. We find the diphoton mass spectrum to be in agreement with the standard model expectation, and set limits on the cross section times branching ratio for the Randall-Sundrum graviton, as a function of diphoton mass. We subsequently derive lower limits for the graviton mass of 230 GeV/c(2) and 850 GeV/c(2), at the 95% confidence level, for coupling parameters (k/M[over](Pl)) of 0.01 and 0.1, respectively.